Suicide commandoes - Poe, Fernando, Jr.; Vasquez, Romeo; Estrada, Joseph; Garcia, Armando; Laxa, Espiridion (Manila Aquarius Records & Tapes, 1962)
Their task is to destroy the airport and bring Lt. Raul Toledo (Romeo Vasquez) safe to a certain destination. The Suicide Commandoes have to risk everything to fulfill this mission and compliment each other. The struggle is really tough and nobody knows what the future holds, and nobody could question their conviction.
DVD
Producer, Espiridion Laxa ; music, Francisco Buencamino ; director, Armando Garcia.
Fernando Poe Jr., Romeo Vasquez, Joseph Estrada.
Keywords: Suicide commandoes (Motion picture).; Action and adventure films; Feature films